2013
DOI: 10.1016/j.devcel.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Rbx2 Regulates Neuronal Migration through Different Cullin 5-RING Ligase Adaptors

Abstract: Morphogenesis requires the proper migration and positioning of different cell types in the embryo. Much more is known about how cells start and guide their migrations than how they stop when they reach their destinations. Here we provide evidence that Rbx2, a subunit of the Cullin5-RING E3 ubiquitin ligase (CRL5) complex, stops neocortical projection neurons at their target layers. Rbx2 mutation causes neocortical and cerebellar ectopias dependent on Dab1, a key signaling protein in the Reelin pathway. SOCS7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 46 publications
4
77
0
1
Order By: Relevance
“…Consistent with this, we found that Gmip KD increased both the frequency of saltatory movements, by shortening the pause duration, and the stride length, both of which led to an increase in the speed of neuronal migration from the V-SVZ to OB. Similar regulatory mechanisms may also affect neuronal migration in other brain regions, such as the Cullin-5-mediated saltatory movement of radially migrating pyramidal neurons 7,8 . Thus, our findings suggest that the speed of neuronal migration can be precisely controlled by Gmip-mediated modulation of the stride frequency and length in the saltatory movement of the soma.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we found that Gmip KD increased both the frequency of saltatory movements, by shortening the pause duration, and the stride length, both of which led to an increase in the speed of neuronal migration from the V-SVZ to OB. Similar regulatory mechanisms may also affect neuronal migration in other brain regions, such as the Cullin-5-mediated saltatory movement of radially migrating pyramidal neurons 7,8 . Thus, our findings suggest that the speed of neuronal migration can be precisely controlled by Gmip-mediated modulation of the stride frequency and length in the saltatory movement of the soma.…”
Section: Discussionmentioning
confidence: 99%
“…Reelin induces tyrosine phosphorylation of Dab1 through ApoER2/VLDLR (26,27,33,34), and phosphorylated Dab1 is quickly degraded by the ubiquitin-proteasome system (37)(38)(39)(40). Dab1 degradation is critical for the termination of neuronal migration (39).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated Dab1 is quickly degraded in the cytoplasm (37)(38)(39)(40), and, thus, the amount of Dab1 reflects the extent of Reelin signaling (26,33,37,40). If N-t cleavage is the major inactivation mechanism for Reelin, the duration of Reelin-PD activity should exceed that of Reelin-WT.…”
Section: Determination Of the N-t Cleavage Site Of Reelin-mentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic SOCS7 deletion can also increase insulin sensitivity by stabilizing IRS proteins, which mediate insulin signaling, in pancreatic ␤ cells (127). Conditional knockout of SOCS7 in neural progenitors during brain development altered the migration of specific classes of neurons, consistent with hyper-responsiveness to reelin, a migration-stimulatory factor (128). SOCS7 binds to Dab1, a protein that is phosphorylated at tyrosine in reelin-stimulated neurons, and stimulates ubiquitination of pY-Dab1 in vitro.…”
Section: Cell Regulation By Socs-crl5 Complexes and By Socs Proteins mentioning
confidence: 99%